Development of a methodology to compare and evaluate health and sustainability aspects of dietary intake across countries - Philippi Rosane, Beatriz; Matthiessen, Lea Ellen; Góralska-Walczak, Rita; Kopczyńska, Klaudia; Średnicka-Tober, Dominika; Kazimierczak, Renata; Rossi, Laura; Aboussaleh, Youssef; Bügel, Susanne Gjedsted (Frontiers in Sustainable Food Systems, 2023)
To solve the rising issue of how to feed our planet in the future, we need to enhance our knowledge of peoples' current eating patterns and analyze those in terms of their health and environmental impacts. Current studies about adherence to existing national and global dietary recommendations often lack the ability to cross-compare the results among countries. Therefore, this study aims to develop a methodology to evaluate adherence to food-based dietary guidelines (FBDGs) and the Planetary Health Diet (PHD) on a national level, which can be replicable in different countries. First, national dietary intake data was collected from surveys published by the respective responsible public institutions from five countries (Italy, Denmark, Germany, Morocco, and Poland). Second, food groups represented in the intake data and the FBDGs were mapped to establish a proposal for a new common grouping (i.e., comprehensive food groups) that enables cross-country comparison. Third, dietary intake was compared to the recommendations according to national FBDG and the PHD. The adherence to the recommended diets was assessed using an adapted version of the German Food Pyramid Index. Our results show that different ways of grouping foods may change adherence levels; when measuring adherence to the FBDGs with the food groups suggested in the FBDGs, average scores (45.5 ± 5.4) were lower than by using comprehensive food groups (46.9 ± 3.7). Higher adherence to the PHD (52.4 ± 6.1) was found also using the comprehensive food groups. Particularly the foods meats, eggs, and legumes in one group (i.e., protein equivalents) appear to influence the outcome of scores using the comprehensive food groups. This study developed a methodology to evaluate national dietary intake against national FBDGs and the PHD. Our study points out the fact that it is difficult to overcome the challenge that countries have different food grouping clusters. Yet, the combination of the methods developed enables cross-country comparisons and has the potential to be applied to different national settings globally.